A Prospective Study Comparing Two Fascial Reconstruction Techniques to Stabilise the Cranial Cruciate Deficient Stifle in the Dog - Coetzee, G. L.; Lubbe, A. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
The standard intra-articular “underand-over” (U & O) cranial cruciate ligament substitute technique, using autogenous fascia lata, was compared with a combined intra- and extracapsular U & O fascial reconstruction procedure. Medium, large and giant dog breeds (body weights ≥ 15 kg), presented with unilateral rupture of the cranial cruciate ligament, were included in the study. Functional usage of the operated limb was evaluated according to a clinical grading system within the first six weeks and again at 12 and 26 weeks after the operation.Dogs treated with the standard intraarticular U & O procedure were partly weight-bearing on the operated limb within three to five weeks postoperatively. Return to full use of the limb with no or only mild, occasional lameness was recorded in 20 of 24 dogs (83.3%) after 26 weeks. Those treated with the combined intra- and extracapsular U & O procedure, returned to partial weight-bearing within four to seven weeks after the operation. These dogs exhibited slightly more cranial drawer motion (± 1.0 - 2.0 mm) at the six- and 12-week follow-up examinations, when compared to the first group, but stifle stability improved between 12 and 26 weeks. The results obtained from 45 of 55 dogs (81.9%) treated with the combined intra- and extracapsular U & O technique were comparable with the standard intra-articular U & O procedure with return to full use of the limb after 26 weeks. Radiological evidence of peri-articular osteophyte formation showed no remarkable difference between the two techniques after 26 weeks. Results obtained from the standard intra-articular U & O technique indicated that it was an effective method for use in large dogs with body weights greater than 30 kg. This is in agreement with findings in other studies. The combined intra- and extracapsular U &O fascial reconstruction was a reliable alternative for use in the medium to large dog breeds with body weights ranging between 15 and 26 kg.The standard intra-articular “under-and-over” (U & O) replacement technique was effective for use in dogs with body weights (BW) >30 kg. Dogs treated with the combined intra- and extracapsular U & O method had slightly more cranial drawer motion at the six-week and 12-week examinations, but stifle stability improved between 12 and 26 weeks, especially in medium-sized to larger dogs with BW ranging between 15 and 26 kg.
Keywords: Cranial cruciate ligament; fascial reconstruction; stifle; dog